Evaluating Urban Green Space Dynamics in Makassar City Through NDVI-Based Analysis of Sentinel-2 Imagery - Edra, Anggun Purnama; Azzahra, Cantika; Nurhayati, Shifa (IJISTECH (International Journal of Information System and Technology), 2025)
Urban expansion in rapidly growing cities like Makassar has considerable implications for vegetation loss and ecosystem degradation. This study investigates vegetation cover changes in Makassar City by analyzing the Normalized Difference Vegetation Index (NDVI) derived from Sentinel-2 imagery for the years 2020 and 2024. A threshold of NDVI > 0.5 was applied to identify areas classified as dense vegetation. Image pre-processing, NDVI computation, and binary classification were performed to quantify and map vegetation extent. The analysis reveals a noticeable reduction in densely vegetated areas. This study analyzes the changes in vegetation health in Makassar City using the Normalized Difference Vegetation Index (NDVI) for the years 2020 and 2024. The NDVI threshold of >0.5 was used to identify areas of healthy vegetation. The spatial analysis and classification maps reveal a significant decline in vegetated areas, with a decrease from 4,792.93 hectares in 2020 to 1,157.23 hectares in 2024. This trend highlights a substantial reduction in healthy vegetation cover, potentially caused by urban development, land-use changes, and environmental pressures. The findings underscore the need for sustainable land management and green infrastructure policies to mitigate the adverse effects of vegetation loss and promote ecological balance in urban areas.